2013
DOI: 10.1186/1471-2180-13-125
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically active Rho and Rac small-GTPases are involved in the establishment of the vacuolar membrane after Toxoplasma gondii invasion of host cells

Abstract: BackgroundGTPases are the family of hydrolases that bind and hydrolyze guanosine triphosphate. The large Immunity-related GTPases and the small GTPase ADP-ribosylation factor-6 in host cells are known to accumulate on the parasitophorous vacuole membrane (PVM) of Toxoplasma gondii and play critical roles in this parasite infection, but these GTPases cannot explain the full extent of infection.ResultsIn this research, RhoA and Rac1 GTPases from the host cell were found to accumulate on the PVM regardless of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 49 publications
(63 reference statements)
1
27
0
Order By: Relevance
“…After that, T. gondii recruits host cell microtubules to form conduits, along which host organelles are transported to the PV (Coppens et al, 2006). The RacGTPases were activated upon T. gondii invasion, and when F-actin polymerization was inhibited in NSC23766-treated cells, the efficiency of T. gondii attachment, invasion, and replication was significantly decreased (Na et al, 2013;Wei et al, 2019). Furthermore, it has been reported that six human proteins (PTK9L, MAPK7, PHPT1, MYLIP, PTPRR, and PPIL2) facilitate T. gondii entry by modifying host actin dynamics (Gaji et al, 2013).…”
Section: The Screened Hdfs Function In Actin Reorganizationmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, T. gondii recruits host cell microtubules to form conduits, along which host organelles are transported to the PV (Coppens et al, 2006). The RacGTPases were activated upon T. gondii invasion, and when F-actin polymerization was inhibited in NSC23766-treated cells, the efficiency of T. gondii attachment, invasion, and replication was significantly decreased (Na et al, 2013;Wei et al, 2019). Furthermore, it has been reported that six human proteins (PTK9L, MAPK7, PHPT1, MYLIP, PTPRR, and PPIL2) facilitate T. gondii entry by modifying host actin dynamics (Gaji et al, 2013).…”
Section: The Screened Hdfs Function In Actin Reorganizationmentioning
confidence: 99%
“…For example, as T. gondii lacks the enzymes for polyamine, arginine, and purine biosynthesis, the intracellular parasites have to get these nutrients from their host cells (Schwartzman and Pfefferkorn, 1982;Fox et al, 2004;Cook et al, 2007). We previously reported that host RhoA and Rac1 GTPases were activated upon T. gondii infection and facilitated T. gondii invasion (Na et al, 2013;Wei et al, 2019). It also has been reported that host hypoxia-inducible transcription factor 1 (HIF-1)/hexokinase 2 (HK2) can reprogram the host cell's metabolism to create an environment conducive for parasite replication at 3% physiological oxygen levels (Menendez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…26 The small GTPases, including Rho, Rac, and adenosine diphosphate-ribosylation factor 6, have been reported to accumulate on the PVM and function in host cell cytoskeleton reorganization during T. gondii invasion, which facilitates PV formation and enlargement in the host cell. 13,14 Interestingly, the GO term "cytoskeletal protein binding" was enriched in all comparisons (M versus L, H versus L, and H versus M), which suggested that host cell cytoskeletal FIGURE 3. Gene ontology (GO) enrichment analysis of the 892 identified phosphoproteins.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that the maintenance of host cell actin cytoskeleton integrity is important for parasite invasion and successful penetration of host cells by apicomplexans; during this process, significant host cell cytoskeletal reorganization is accompanied. 13,14,27 Toxoplasma gondii infection induces and maintains a "proliferation response" including dysregulation of the cell cycle in infected host cells. This response may fulfill critical growth and multiplication requirements of the parasite during intracellular residence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation